2008
DOI: 10.1007/s10840-008-9280-8
|View full text |Cite
|
Sign up to set email alerts
|

Successful transition to buprenorphine in a patient with methadone-induced torsades de pointes

Abstract: A 56-year-old-man presented with syncope and torsades de pointes secondary to methadone-induced QT prolongation. After transition from methadone to buprenorphine, a partial mu-opiate-receptor agonist and a kappa-opiate-receptor antagonist, the QT normalized and ventricular arrhythmias resolved. Buprenorphine should be used for opiate dependence and chronic pain in patients with methadone-induced QT prolongation and as first line therapy in patients with risk factors for torsades de pointes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Another study indicated that buprenorphine is a safe drug in common daily doses (11 ± 5 mg) [37]. Encouraging the idea of choosing buprenorphine over methadone, a case report showed that buprenorphone was able to settle QT prolongation and ventricular arrhythmia secondary to methadone [38]. Thus, based on the studies mentioned above, buprenorphine at conventional doses, by itself, does not appear to produce clinically significant QT interval prolongation and arrhythmia, and is a safe drug in this respect.…”
Section: Prolongation Of Qt Interval and Ventricular Arrhythmiamentioning
confidence: 99%
“…Another study indicated that buprenorphine is a safe drug in common daily doses (11 ± 5 mg) [37]. Encouraging the idea of choosing buprenorphine over methadone, a case report showed that buprenorphone was able to settle QT prolongation and ventricular arrhythmia secondary to methadone [38]. Thus, based on the studies mentioned above, buprenorphine at conventional doses, by itself, does not appear to produce clinically significant QT interval prolongation and arrhythmia, and is a safe drug in this respect.…”
Section: Prolongation Of Qt Interval and Ventricular Arrhythmiamentioning
confidence: 99%
“…The curves represent the prediction based on a f u,p of 0.22 (black line), 0.15 (red line), 0.055 (blue line) and 0.034 (green line). Symbols represent the data obtained from case reports, case series of individuals (orange triangles) (Esses et al 2008 ; Fredheim et al 2006 ; Krantz et al 2002 ) and other studies as follows: Bart et al ( 2017 ) (purple circle); Carlquist et al ( 2015 ) (orange square); Chang et al ( 2012 ) (green circle) Chowdhury et al ( 2015 ); (dark blue cross); Cruciani et al ( 2005 ) (green cross) Eap et al ( 2007 ); (green star); Ehret et al ( 2006 ) (dark blue triangle) Fareed et al ( 2013 ); (dark blue circle) Heesch et al ( 2015 ); (dark blue star) Krantz et al ( 2005 ); (orange circles) Maremmani et al ( 2005 ); (green square); Martell et al ( 2005 ) (green triangle) Peles et al ( 2007 ); (orange star); Reddy et al ( 2010 ) (orange circles) Roy et al ( 2012 ); (dark blue square). The in vivo data are summarized in Table S1 and S2 (color figure online) …”
Section: Resultsmentioning
confidence: 99%
“…The curves represent the prediction based on a f u,p of 0.22 (black line), 0.15 (red line), 0.055 (blue line) and 0.034 (green line). Symbols represent the data obtained from case reports, case series of individuals (orange triangles) (Esses et al 2008;Fredheim et al 2006;Krantz et al 2002) and other studies as follows: Bart et al (2017) Table S1 and S2 (color figure online) Fig. 9 Comparison of BMDL values derived from the predicted dose-response curves for human cardiotoxicity of methadone presented in Fig.…”
Section: Evaluation Of the Pbk Modeling-based Reverse Dosimetry Appromentioning
confidence: 99%
“…Additionally, other studies depict differences regarding quality of life, which seem to improve more positively amongst patients treated with B/N than amongst MT patients 76 . B/N use seems also better than MT therapy as far as security is concerned, for it features lower overdose 36,50,[77][78][79] and QT interval prolongation [80][81][82][83][84] risks. As regards the interaction profile, B/N is globally better than MT 85 and it can be prescribed without causing withdrawal syndrome amongst HIV infected patients when combined with non-nucleoside reverse transcriptase inhibitors (NNRTI), such as efavirenz or nevirapine 86 .…”
Section: Differences Between Mt and B/n Usementioning
confidence: 99%